Neuropsychological variables and clinical status in anorexia nervosa: relationship between visuospatial memory and central coherence and eating disorder symptom severity - Zuchova, Svetlana; Kubena, Ales Antonin; Erler, Theodore; Papezova, Hana (Eating and weight disorders, 2013)
AIM: To explore the relationship between visuospatial memory, weak central coherence, and eating disorder (ED) symptoms in anorexia nervosa (AN) inpatients. SAMPLE: 31 female AN inpatients. METHODS: Rey complex figure test (RCFT) was used to assess both visuospatial memory and central coherence. RCFT consisted of copy and recall trials. ED symptoms were assessed by The Eating Disorder Examination-Questionnaire (EDE-Q) and The Clinical and Research Inventory for Eating Disorders (CR-EAT). RESULTS: We found a statistically significant negative correlation between recall accuracy and the total EDE-Q score. Furthermore, recall accuracy and recall central coherence significantly negatively correlate with several EDE-Q and CR-EAT scales. CONCLUSIONS: These findings may contribute to a better understanding of cognitive impairments specifically in ED, and to refining interventions aiming at their improvement.
Keywords: dospělí; Sense of Coherence; Female; životní smysluplnost; Neuropsychological Tests; Adult; sebepojetí; ženské pohlaví; Self Concept; Adolescent; neuropsychologické testy; lidé; Memory; mentální anorexie; stupeň závažnosti nemoci; Personality Inventory; představa o vlastním těle; Body Image; paměť; Anorexia Nervosa; osobnostní dotazník; Severity of Illness Index; mladiství; Humans